An introduction for system developers to volunteer roles in crisis response and recovery - Rogstadius, Jakob; Teixeira, Claudio A.; Karapanos, Evangelos; Kostakos, Vassilis (My University, 2013)
Technological advances, such as software tools for citizen reporting, first responder support, and online collaborative information management and mapping, are enabling new or improved forms of volunteering in humanitarian crisis. However, the change is largely driven by the technical community and many proposed solutions are never integrated into community response efforts, indicating mismatches between designs and real world needs. This paper offers readers with a technical background insight into roles, goals and constraints of humanitarian crisis response. In particular, we present three seemingly conflicting views regarding how citizens can contribute to response activities as spontaneous volunteers. With examples from two field studies and grounded in literature review, we integrate the three viewpoints into a framework explaining how the roles of volunteers and trained professionals shift with increasing severity and scale of a crisis. Based on this framework, we also discuss high-level opportunities for supporting crisis response with new software tools.
Keywords: Collaboration; Crisis management; Developer guidelines; Disaster response; System development; Volunteering